To Leave or Not to Leave? A Multi-Sample Study on Individual, Job-Related, and Organizational Antecedents of Employability and Retirement Intentions - Le Blanc, Pascale M.; Peeters, Maria C. W.; Van der Heijden, Beatrice I. J. M.; van Zyl, Llewellyn E. (Frontiers in Psychology, 2019)
In view of the aging and dejuvenation of the working population and the expected shortages in employees’ skills in the future, it is of utmost importance to focus on older workers’ employability in order to prolong their working life until, or even beyond, their official retirement age. The primary aim of the current study was to examine the relationship between elderly workers’ employability (self-)perceptions and their intention to continue working until their official retirement age. In addition, we studied the role of potential antecedents of their perceived employability at three different levels: training and education in current expertise area as well as in an adjacent expertise area (individual level factor), learning value of the job (job level factor), and organizational career management practices (organizational level factor). Data were collected by means of e-questionnaires that were distributed among two groups of Dutch older (45-plus) white collar workers. The samples consisted of 223 employees of an insurance company, and 325 university workers, respectively. Our research model was tested separately in each sample using Structural Equation Modelling; in our analyses, we controlled for the effects of respondents’ (self-)perceived health and (self-)perceived financial situation. Similar results were found for both samples. First, the relationship of perceived employability with the intention to continue working until one’s retirement age was positive, whereas the relationship between a perceived good financial situation with the intention to continue working until one’s retirement age was negative. Secondly, as regards the potential antecedents, results showed that the learning value of the job was positively related to perceived employability. In addition, an employee’s perception of good health is a relevant correlate of perceived employability. So, whereas perceived employability contributes to the intention to continue working until one’s retirement age, a perceived good financial situation is a push factor to retire early. In order to promote the labour participation of older workers, this study indicates that organizations should focus on the learning possibilities that are inherent to one’s job rather than on providing additional training or career management. Further research is needed to test the generalizability of our results to other samples.